Direct economic benefits and human dependence toward Gunung Merapi National Park, Indonesia - Ruky Umaya; Hardjanto; Rinekso Soekmadi; Satyawan Sunito (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Umaya R, Hardjanto, Soekmadi R, Sunito S. 2020. Direct economic benefits and human dependence toward Gunung Merapi National Park, Indonesia. Biodiversitas 21: 982-993. Merapi (Java, Indonesia) is recognized as the most active volcano in Indonesia. This area has also gazetted as a national park, called Gunung Merapi National Park (GNMP), despite the existence of humans who live adjacent to the park with high dependency on its resources. The objectives of this study were to determine direct use value (DUV) and investigate human dependence toward the goods and services generated from GNMP. The research was conducted in 27 sub-villages. In total 277 respondents and 62 key informants were selected using purposive sampling and 9 times focus group discussion. The DUV was estimated using market price approach. The results of this study found that the DUV of GMNP was IDR 87,947,589,505 year-1, generated from direct benefit of grasses for animal feedstock (41.74%), sand mining (31.32%), water consumption (20.23%), fuelwood collection (3.57%), ecotourism activities (1.65%), land management for agriculture (1.48%), and orchid conservation program (0.01%). The dominance of DUV derived from grasses collection, sand mining and water consumption was highly correlated with the characteristics of sub-villages communities, influenced by the events of eruption of Merapi volcano, changes in legal status of forest function and market situations. Sub-village communities have historically developed reciprocal relationships with Merapi volcano and its surrounding ecosystem in terms of ecological, economic, and cultural aspects, and they played important roles in natural resources management of Merapi volcano. The findings of this study suggest that an important strategy for GMNP authority is by positioning sub-village communities and their norms as resource beneficiaries and partners in managing the park, highlighting that their existence should not be neglected.